Case report: Antiplatelet therapy on metastatic paraganglioma-associated cutaneous vascular disease and literature review - Gao, Yinjie; Cui, Yunying; Hu, Zhonghui; Wang, Yu; Li, Tianyi; Liu, Yuehua; Tong, Anli (Frontiers in Medicine, 2022)
Context Tumor-associated cutaneous vascular disorder induced by PPGL was extremely rare, and the cutaneous manifestations could disappear after removal of the tumors. However, the definite pathological diagnosis and the potential mechanism remained unidentified. We presented a severe cutaneous vascular lesion manifested as diffuse erythema with ulceration and necrosis over the limbs in a female patient with metastatic paraganglioma. Skin biopsy was performed on her for defining the pathological diagnosis and potential mechanism. The patient was diagnosed as vascular disease according to the obvious angioectasia in dermis on cutaneous pathology, which might be caused by PPGL-induced hypercoagulability. We used the antiplatelet therapy with aspirin to treat the PPGL-associated cutaneous vascular disease for the first time, and the cutaneous lesions were relieved and healed gradually, further supporting the diagnosis of vascular disease. Conclusion For metastatic PPGL patients like the case we reported, the definite diagnosis by skin biopsy and the early antiplatelet therapy might be effective to the cutaneous lesions caused by the hypercoagulable state of PPGL.